2018
DOI: 10.1111/ijfs.13976
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR and Raman spectroscopy of oils and extracts obtained from organic and conventional goji berries: yield, fatty acids, carotenoids and biological activities

Abstract: The yields of extraction, fatty acid and carotenoid compositions, antioxidant and antimicrobial activities of organic and conventional Lycium barbarum oils and extracts were investigated. Different methods were used in the extraction: Soxhlet, maceration and Bligh & Dyer. Sample characterization was performed by proton nuclear magnetic resonance and Raman spectroscopy. Soxhlet presented a higher yield for organic (4.58%) and conventional (2.83%) fruit. The Goji samples showed a high content of unsaturated fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Linoleic acid was the most abundant fatty acid in L. barbarum seed oil, which was an essential fatty acid and basic component involved in the architecture and function of cellular membranes (Choque et al., 2014). The linoleic acid content was consistent with previously reported data (Li et al., 2011; Yunusova et al., 2020) and was higher than that from the fruit (54.20−61.87%) (Pedro et al., 2018). The total unsaturated fatty acids reached up to 88%.…”
Section: Resultssupporting
confidence: 91%
“…Linoleic acid was the most abundant fatty acid in L. barbarum seed oil, which was an essential fatty acid and basic component involved in the architecture and function of cellular membranes (Choque et al., 2014). The linoleic acid content was consistent with previously reported data (Li et al., 2011; Yunusova et al., 2020) and was higher than that from the fruit (54.20−61.87%) (Pedro et al., 2018). The total unsaturated fatty acids reached up to 88%.…”
Section: Resultssupporting
confidence: 91%
“…One of the most important components are polysaccharides, which has been proved to have a large variety of bioactivities, such as protection against irradiation injury (Li et al, 2007), antivirus (Wang, Hu, et al., 2010), antioxidant activity (Liang et al., 2011), hypoglycemic effect (Zhu et al., 2013), modulating immune response (Ding et al., 2019), and as novel candidate prebiotic (Zhou et al., 2018). The composition of other bioactive components derived from goji berry fruits, like the widely distributed carotenoids, polyphenols, dicaffeoyl polyamine derivatives, ascorbic acid derivatives, and fatty acids have been studied in depth (Huang et al., 2019; Li et al., 2019; Pedro et al., 2019; Qian et al., 2020; Wang et al., 2010; Zhang et al., 2016; Zhao et al., 2020; Zhou et al., 2017). Given the great health‐enhancing effect, there has been a growing trend in the consumption of goji berry fruits and their products.…”
Section: Introductionmentioning
confidence: 99%
“…dicaffeoyl polyamine derivatives, ascorbic acid derivatives, and fatty acids have been studied in depth (Huang et al, 2019;Li et al, 2019;Pedro et al, 2019;Qian et al, 2020;Zhang et al, 2016;Zhao et al, 2020;Zhou et al, 2017). Given the great health-enhancing effect, there has been a growing trend in the consumption of goji berry fruits and their products.…”
mentioning
confidence: 99%
“…The higher content of bioactive compounds, such as flavonoids, in the yellow goji berry extract, is probably associated with its prominent antibacterial potential compared to other analysed extracts [66]. In addition, Pedro et al [67] showed that organic goji berry oils and extracts showed higher antimicrobial activity in comparison with samples of conventional fruits, which can be explained by the highest contents of fatty acids and carotenoids. So, the observed antibacterial potential of yellow goji berry could be attributed to the highest UFA and linoleic acid content.…”
Section: Antimicrobial Activitiesmentioning
confidence: 97%